Effects of 3 months of full-court and half-court street basketball training on health profile in untrained men - Morten B. Randers; Marie Hagman; Jonathan Brix; Jesper F. Christensen; Mogens T. Pedersen; Jens J. Nielsen; Peter Krustrup (Elsevier, 2018)
Purpose: The aim of the present study was to investigate whether street basketball organized as 3 v 3 on either a half court (HC) with 1 basket or a full court (FC) with 2 baskets could improve fitness and health profiles of untrained men after 3 months of supervised training. Methods: Thirty-five untrained men (aged 20-42 years) completed the pre- and post-intervention testing (FC: n = 13, HC: n = 12, CO (control): n = 10). The training attendance was 2.0 ± 0.4 and 1.9 ± 0.3 times per week in FC and HC, respectively. Mean heart rate (HR) was 83.8 ± 6.0 percent of maximal heart rate (%HRmax) and 84.5 ± 2.9 %HRmax in FC and HC, respectively. Results: The 3 months of street basketball training on an FC with 2 baskets increased maximal oxygen uptake (2.4 mL/min/kg (95% confidence interval (CI): 1.0-3.9)), time to exhaustion (47 s (95%CI: 26-67)), lean body mass (0.8 kg (95%CI: 0.1-1.5)), and bone mineral density (0.021 g/cm2 (95%CI: 0.011-0.031)), whereas mean arterial pressure (-5.6 mmHg (95%CI: -7.5 to 3.7)), body fat percentage (-1.6%, (95%CI: -2.5 to -0.7)), heart rate (-18 bpm (95%CI: -24 to -12)), and blood lactate (median: -1.4 mmol/L (interquartile range: -1.5 to -0.6)) during submaximal running were lowered. The changes were less pronounced after the training period when playing on an HC with 1 basket, but increases in maximal oxygen uptake (1.6 mL/min/kg (95%CI: -0.1 to 3.3)), time to exhaustion (28 s (95%CI: 9-47)), lean body mass (1.3 kg (95%CI: 0.3-2.4)), and lower body fat percentage (-0.9% (95%CI: -1.9 to -0.1)) were observed in this group. Conclusion: Three months of 3 v 3 street basketball training improved fitness and led to broad-spectrum improvements in variables related to overall health profile, with the most marked effects observed when playing on an FC with 2 baskets. Keywords: Blood pressure, Body composition, Cardiovascular fitness, Maximal oxygen uptake, Muscoloskeletal fitness, Physical demands, Small-sided games, Team sport